Local Wisdom Values of the Bugis Community in Early Childhood Multicultural Learning - Musi, Muhammad Akil; Muh. Yusri Bachtiar; Herlina; Sitti Nurhidayah Ilyas (Universitas Pendidikan Ganesha, 2022)
The value of local wisdom contains the noble values of the nation's ancestors that can be used as capital to form a nation with good and strong character. Multicultural education must be provided in schools and educational environments that have equal opportunities regardless of race, ethnicity, language, religion, gender, cultural background, socio-cultural status, and sexual orientation. This study aims to analyses the application of Bugis cultural values ​​in early childhood learning. The research was conducted through a qualitative approach to describe a phenomenon. Data collection was carried out in the form of interviews, observations and document studies through informants at the Kindergarten. The data analysis technique used in this research is interactive model analysis using triangulation to validate the data. The results showed that the multicultural learning curriculum consisted of multiple intelligences, universal values, gender equality, and local wisdom. The values ​​of local wisdom of the Bugis community in early childhood learning are found to be values, namely sipakatau (mutualizing one another), sipakaraja (mutual respect), sipakalebbi (mutual honoring), sipakainge (reminding each other), sipatokkong (generating enthusiasm) and sipakatuwo (supporting each other). The value of local wisdom is integrated in the early childhood learning process.